Power and Relationship:: Two Elements of the Chinese/Western Divide - Miles, Michael (Journal of Comparative International Management)

(untitled) (Management Futures, 2000)
The day on which Zhang Wei Gou met John Redmann was fateful in many ways. Zhang had worked for many years at a small paper factory in Shanxie province. He had a good reputation as a manager of people but the State-owned factory in which he worked was small and very inefficient. Production quality was low, processes were not well thought out and the workers in general were not much interested in improving things. Zhang was frustrated both with his leaders' inability to improve conditions at the factory and with his own inability to change things despite his good relations with the workers. He decided in the summer of 1996 to xiahie (to take a job in the private sector). He quickly found a supervisory job in a China-Canadian joint venture in the nearby city of Xian.